Salt‐Assisted Low‐Temperature Growth of 2D Bi2O2Se with Controlled Thickness for Electronics. Issue 10 (20th December 2022) - Khan, Usman; Nairan, Adeela; Khan, Karim; Li, Sean; Liu, Bilu; Gao, Junkuo
Abstract: Bi2 O2 Se is the most promising 2D material due to its semiconducting feature and high mobility, making it propitious channel material for high‐performance electronics that demands highly crystalline Bi2 O2 Se at low‐growth temperature. Here, a low‐temperature salt‐assisted chemical vapor deposition approach for growing single‐domain Bi2 O2 Se on a millimeter scale with thicknesses of multilayer to monolayer is presented. Because of the advantage of thickness‐dependent growth, systematical scrutiny of layer‐dependent Raman spectroscopy of Bi2 O2 Se from monolayer to bulk is investigated, revealing a redshift of the A 1g mode at 162.4 cm −1 . Moreover, the long‐term environmental stability of ≈2.4 nm thick Bi2 O2 Se is confirmed after exposing the sample for 1.5 years to air. The backgated field effect transistor (FET) based on a few‐layered Bi2 O2 Se flake represents decent carrier mobility (≈287 cm 2  V −1 s −1 ) and an ON/OFF ratio of up to 10 7 . This report indicates a technique to grow large‐domain thickness controlled Bi2 O2 Se single crystals for electronics. Abstract : It is known that the growth of large domains of single crystal 2D materials is important for device integration. Here, salt‐assisted deposition approach is presented to grow atomically‐thin, millimeter size 2D Bi2 O2 Se domains at a low‐temperature. Because of the high quality of the salt‐assisted‐grown material, a few‐layer Bi2 O2 Se‐based FET represents an excellent high on/off ratio of ≈10 7 and mobility of ≈287 cm 2  V −1 s −1 . The results presented in this work, reveal the remarkable potential of 2D Bi2 O2 Se for future 2D electronics.